Longitudinal study of Thai people media exposure, knowledge, and behavior on dengue fever prevention and control - Smith Boonchutima; Kirati Kachentawa; Manasanun Limpavithayakul; Anan Prachansri (Elsevier, 2017)
Dengue hemorrhagic fever is transmitted through a bite by a dengue -infected Aedes aegypti mosquito. It was first reported in the mid -20th century in Thailand, and since then its epidemiology has been of great concern and has spread all across the country. The alarming incidence of dengue posed a serious threat to human health in all major cities of Thailand.This study was aimed at identifying the level of awareness of dengue fever in Thai population knowledge for prevention and control, and most importantly contribution of media in educating masses for dengue control measures. It is longitudinal in nature and was conducted in 25 provinces of Thailand during 2013-2015. Approximately 7772 respondents participated in this study, with the selection of provinces based on considerations like population, prevalence and demography. A pre-tested structured questionnaire was used to collect information relevant to study participants' demographic profile, pre-existing knowledge about dengue fever and its reinforcement through media, and population attitudes toward prevention and control.Over the period of three years, a positive trend was revealed relevant to the contribution of media in educating and reminding the Thai population of dengue, without any uniformity or powerful campaigns. Based on the results drawn from this study, we conclude that despite the measures undertaken to prevent dengue fever, there is insufficient media exposure. An interdisciplinary approach involving the community participation, media, and government is needed to overcome dengue threat in Thailand. Keywords: Dengue, Aedes aegypti, Thailand, Media, Knowledge, Behavior, Prevention, Control